2021
DOI: 10.3390/jpm11101041
|View full text |Cite
|
Sign up to set email alerts
|

TRANS-TACE: Prognostic Role of the Transient Hypertransaminasemia after Conventional Chemoembolization for Hepatocellular Carcinoma

Abstract: The aim of the present study was to correlate laboratory data and postprocedural parameters after conventional transarterial chemoembolization (cTACE) for hepatocellular carcinoma (HCC) with the radiological response. The study consisted of a retrospective analysis of prospectively collected data from 70 consecutive patients who underwent cTACE. Laboratory parameters were assessed daily after cTACE and compared to pretreatment values. Post-treatment radiological response was assessed using mRECIST at one month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…Moreover, the occurrence of adverse events can also predict patient prognosis. Granito et al (30) showed that post-treatment transaminase elevation predicted the objective response to TACE. The results regarding the management of adverse events with TACE+AC and its relationship with prognosis will be reported in our subsequent study.…”
Section: Safetymentioning
confidence: 99%
“…Moreover, the occurrence of adverse events can also predict patient prognosis. Granito et al (30) showed that post-treatment transaminase elevation predicted the objective response to TACE. The results regarding the management of adverse events with TACE+AC and its relationship with prognosis will be reported in our subsequent study.…”
Section: Safetymentioning
confidence: 99%
“…found posttreatment transient transaminase elevation was predictive of objective response to superselective cTACE. But most other studies focus on radiological features or common tumor markers rather than specific biomarkers ( 52 ). Second, few studies focus on the relation between TACE refractoriness and HCC patient outcome, and developed predictors are primarily used for diagnosis rather than prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an elevated De Ritis ratio at baseline reflects tumor progression and deterioration of liver functional reserve. However, the transient elevation of serum transaminases in HCC patients after superselective transarterial chemoembolization was not accompanied by deterioration of liver functional reserve compared with baseline values but was secondary to tumor necrosis resulting in the release of large amounts of serum transaminases, reflecting a response to therapy ( 32 ).…”
Section: Discussionmentioning
confidence: 99%